Translatological Ecosystem of the Region: Determinants, Constituents, Features - Elina Yu. Novikova; Olga I. Popova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The article focuses on the phenomenon of “translatological ecosystem of the region”, which is studied with application of an integrative approach to Translation Studies. Polydiscursive hypertext translation discourse is an integral part of the regional urban discourse and the regional ecosystem on the whole; their interdependence, co-development and interpenetration determine the formation of a special regional ecosystem of translation with distinctive constitutive features. An attempt is made to analyse the factors of formation and development of the regional translatological ecosystem on the example of the Hero City of Volgograd. The hermeneutic and interpretive perspective of the study has enabled identifying and describing various means of regionally conditioned communication actualization with the involvement of translation services, determining the constituent features of the translatological ecosystem and their dominance factors in the urban discourse of the region under study and characterizing this translation ecosystem specificity. The model of the translation ecosystem is presented considering its polydiscursive nature. The system- and city-forming concepts that have an initial impact on the translational action in the region are identified. The translation discourses, which comprise the translatological ecosystem are analysed in detail, industrial, excursion, specialised, educational, social and political ones included. The research contributes to the formation of discursive regional Applied Translation Studies and enhances a novel direction in the science of translation – Eco-Translatology.